Efeitos do uso da terra na diversidade beta de macroinvertebrados aquáticos da bacia hidrográfica do rio Itaqueri, São Paulo, Brasil - Assis, João Vitor de Mello (Universidade Federal de São Carlos, 2022)
Anthropogenic actions within watershed can cause impacts that alter ecosystem functions and negatively impact biodiversity. The beta diversity is useful for analyzing the effects of impacts between communities. The studies presented here were carried out in a watershed with high occupation by agriculture in the Cerrado biome and investigated the effects of land uses on the beta diversity of aquatic macroinvertebrates. In the first study, patterns of turnover and nestedness between tributary streams and reservoir were analyzed. Considering the direct influences of land uses on the community structure of the streams, the hypothesis was tested that the turnover and nestedness of communities in the reservoir would respond directly to the changes that occurred in the streams communities. The second study we analyzed the functional beta diversity with the action of the environmental filters of the watershed. Considering that land uses work as filters that select functional traits, it was asked which traits would relate to different land uses. Ten points were sampled, between streams and the reservoir and in the rainy and dry periods. The environmental variables of water were analyzed, determining the percentages of land use in the entire watershed and in the surroundings of each point. Most macroinvertebrates were identified down to the family level and family Chironomidae down to the genus level, and six categories of functional traits were used. The results of the frist study showed that the patterns that occurred in the streams did not directly influence the communities in the reservoir. Land uses and pollution prevented dispersal. The results of the second study indicated that only the body length trait was positively correlated with perennial agriculture and wetlands. However, there was a predominance in the community composition of a resilient trait and a seasonal increase in genera considered to be tolerant. The studies here demonstrated the considerable level of environmental degradation and impacts on the biodiversity of the watershed.
Effects of land use on the beta diversity of aquatic macroinvertebrates from the Itaqueri Watershed, São Paulo, Brazil
Keywords: Diversidade beta; Usos da terra; Macroinvertebrados; Agricultura; Microbacia; Beta diversity; Land use; Macroinvertebrates; Agriculture; Watershed; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS